Steedman’s Temporality Proposal and Finite Automata - Fernando, Tim (Proceedings of the Amsterdam Colloquium, 2011)
The proposal from Steedman 2005 that “the formal devices” required for temporality in linguistic semantics “are those related to representation of causality and goal-directed action” is developed using finite automata, implicit in which are notions of causality (labelled transitions) and goal-directed action (final/accepting states). Three strands in theories of aspect isolated in Binnick 2006 are examined: temporal relations, phases, and boundedness. The commonly held dichotomy between states and events is linked to that between programs and their runs, as strings representing events are extended to automata.